Selumetinib in patients receiving standard pemetrexed and platinum-based chemotherapy for advanced or metastatic KRAS wildtype or unknown non-squamous non-small cell lung cancer: A randomized, multicenter, phase II study. Canadian Cancer Trials Group (CCTG) IND.219. (July 2019) - Melosky, Barbara; Bradbury, Penelope; Tu, Dongsheng; Florescu, Marie; Reiman, Anthony; Nicholas, Garth; Basappa, Naveen; Rothenstein, Jeffrey; Goffin, John R.; Laurie, Scott A.; Wheatley-Price, Paul; Leighl, Natasha; et al.
Highlights: No difference in efficacy/toxicity for intermittent or continuous selumetinib. Combination of selumetinib and platinum associated with higher ORR in first line. No association between KRAS status and efficacy. Skin and GI adverse events were more common with addition of selumetinib. High incidence of venous thromboembolism was seen in all arms. Abstract: Introduction: Activation of the RAS/RAF/MEK/ERK pathway may confer resistance to chemotherapy in non-small cell lung cancer (NSCLC). Selumetinib (AZD6244, ARRY142886), a MEK1/2 inhibitor combined with chemotherapy in patients with NSCLC was evaluated in two schedules to evaluate efficacy and toxicity. Methods: IND.219 was a three-arm study of first line pemetrexed/platinum chemotherapy with two schedules of selumetinib (Arm A: intermittent given on days 2–19; Arm B: continuous given on days 1–21) versus chemotherapy alone (Arm C). The primary endpoint was objective response rate (ORR); secondary objectives were tolerability, progression-free survival (PFS), overall survival (OS). The trial was stopped at the planned interim analysis. Results: Arms A/B/C enrolled 20/21/21 patients, ORR was 35% (95% CI 15–59% median duration 3.8 months), 62% (95% CI 38–82%; median duration 6.3 months), 24% (95% CI 8–47%; median duration 11.6 months) respectively. The PFS (months Arm A, B, C) was 7.5, 6.7, 4.0 respectively (hazard ratio (HR) PFS Arm A over Arm C: 0.76 [95% CI, 0.38–1.51, 2-sided p = 0.42]; Arm B over Arm C 0.75 [95% CI 0.37–1.54, p = 0.43]. Skin and gastrointestinal adverse events were more common with the addition of selumetinib. A high incidence of venous thromboembolism was seen in all arms. Conclusions: Selumetinib combined with chemotherapy was associated with a higher response rate. Continuous selumetinib appeared to be superior to an intermittent schedule. PFS was prolonged with the addition of selumetinib, however this was not statistically significant.